Changes in Vegetation Cover and the Feeding Preferences of African Elephants in Rimoi Game Reserve, Kenya - J. A. , Koskey; Owuor , Okeyo J. B; V. , Sudoi; S. J, Koskey . (African Journal of Education,Science and Technology (AJEST), 2015)
Tree cover is decreasing in several African savannas due to high elephant pressure. Outside protected areas the situation is even worse due to anthropogenic activities. Reduction in tree cover could have serious consequences if trees have positive effects on herbivore food quality and availability. In East Africa woodlands have been changed to open grasslands in areas with elephants due to selective suppression of the regeneration of desirable species. This threatens the productivity of these ecosystems thereby affecting biological diversity. This study was conducted in Rimoi Game Reserve, Elgeyo Marakwet County, Kenya in 2010. Landsat images were downloaded from the global land cover facility using path 169 and row 060. The down loaded image was projected using coordinates WGS 84 Zone 36 N. the bands used were 2, 3 and 4 because vegetation reflects better in NIR band. These bands were clipped to study area shape file and false colour composite which were prepared using bands 2, 3 and 4. To enhance detail legibility during classification, the area was classified using Anderson classification scheme based on three classes: Trees, woodlands and shrubs. This was done in Arc GIS 9.3 and processed using Erdas imagine 9.2, so as to get classified maps, NDVI and change maps. Results showed that there was moderately strong change between 1986 and 2000 (Cramer‘s V= 0.328) indicating relationship between change in 1986 and 2000 (Kappa = 0.065). The change between 2000 and 2006 was also strong (Cramer‘s V = 0.358), indicating that the relationship between change in 2000 and 2006 was strong (Kappa = -0.187). The change between 1986 and 2006 was very strong (Cramer‘s V = 0.400), indicating that there was a strong agreement in association between changes during this period (Kappa = -0.15561).